أحكام النفقة في الفقه الإسلامي والقانون الجزائري - الامام, عبد الحق; عبد الكريم, بوخلط; بلخير, بالحبيب; يوسف, قصبة (University of Eloued-جامعة الوادي, 2015)
تعتبر النفقة حق وواجب أمر بها الشرع وبين مفهومها وأدلة وجوبها ومستحقيها ، وقد بينا هذا في بحثنا ، كما تطرقنا ل أ ري المشرع الج ا زئري في النفقة . بعدها تطرقنا إلى أقسام النفقة ) الزوجية ونفقة الأقارب ( حيث عرفنا كل قسم وبينا حكمه وشروط وجوبه ، وكيفية تقدير النفقة في الفقه الإسلامي والقانون الج ا زئري ، بعدها وضحنا بعض أحكام النفقة وكيف عالجها الشرع والقانون الج ا زئري . وأخي ا ر تكلمنا عن الأسباب التي تؤدي إلى سقوط حق النفقة ، وكيف تعامل القانون مع من امتنع عن أداء النفقة الواجبة عليه . Considered alimony right and duty ordered by shara and between concept and eoidence that it is obligatory , and those who deserve it in Islamic jurisprudence and law Algerian , and we have explained this in our research , then we dealt with the maintenance sections where we knew each section and pena concept reigh terms obligatory and how appreciation in Islamic jurisprudence and law , then we explained some of the provisions of alimony and law they dealt with al – shara and the law . and finally we talked about the reasons that lead to the fall of the right to alimony and how they deal law with refrains on the performance of obligatory spending it
شريعة وقانون